(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Asthma is a non-communicable inflammatory airway disorder in which patients present with recurring boutsof breathlessness and wheezing. IL-23 is a proinflammatory cytokine its biological functions have beenwell known for the capability to enhance Th17 cell functions. Current study aimed to estimate the geneexpression and serum level of IL-23 and to investigate whether IL-23 plays pivotal roles in the developmentof asthma in asthmatic Iraqi childhood . This study was conducted on two groups: seventy five asthmapatients (27 female and 48 male) and twenty five apparently healthy as a control group (10female and 15male).The age of the samples ranged from (1-10) years old. Recruited from admitting the Central TeachingHospital Pediatrics and Alzahra’a Center for Asthma Allergy in Baghdad during the period extended fromOctober /2019 to last February/2020. Subject information’s were collected using a specific questionnaireform as a descriptive study; on the other hand, the present study was approved by the council of instituteof genetic engineering and biotechnology for post graduate studies / University of Baghdad. The RNA wasextracted from the blood sample of asthma patients and apparently healthy subjects by using TransZol UpPlus RNA Kit (blood) .The acceptable purity of RNA in asthmatic patient is range between 1.84-1.99 and forapparently healthy group is range between 1.84-1.96.mRANA expression were determined by real time PCRassay and detect the concentration of IL-23 using ELISA technique. For IL-23 gene expression that showedthe Ct of asthma patient group (22.82) and control group (23.33) and the 2-??Ct of asthma patient group(5.35) and control group (3.70) and the fold of gene expression was statistically significantly (P?0.05).in the asthmatic group than healthy non asthmatic group that show in ratio (1.44: 1.00) . Human IL23concentration was estimated by ELISA, the results were statistically significant (P?0.002), the level ofIL-23 in asthma patient group (451.80 ± 91.80pg/ml) while the level of IL-23 in Control group(182.36 ±58.21 pg/ml) as well as increase concentration of IL-23 in severe asthma patients than mild form asthma726.91 ± 142.98 and 133.72 ± 79.56 respectively.